EVALUATION OF VARIOUS INORGANIC MEDIA FOR GROWTH AND BIOPIGMENTS OF DUNALIELLA SALINA - JYOTI KULSHRESHTHA; GAJENDRA PAL SINGH (International Journal of Pharma and Bio Sciences, 2013)
Dunaliella salina is a unicellular green microalga that is considered as one of the best commercial sources of carotenoids. Growth and pigment production of D. salina (isolated from Sambhar Salt Lake, Rajasthan) was studied by using various inorganic media differing in chemical compositions viz. Artificial Sea Water media, De Walne’s media, Johnson’s media, AS-100 and Modified Bold’s Basal media. The best growth with highest pigment production was observed in the artificial sea water medium as compared to other media.